Ellis-Van Creveld Syndrome, neonatal teeth and breastfeeding impairment: a case report - Renata Zoraida Rizental DELGADO; Ana Carolina Fernandes COUTO; Romulo Andrade MARCATO; Danielle PORTINHO; Wanda Terezinha Garbelini FROSSARD; Cássia Cilene Dezan GARBELINI (Faculdade São Leopoldo Mandic, 2021)
ABSTRACT Because of multisystemic impairment in patients with Ellis-van Creveld syndrome, multidisciplinary care may be demanded since birth to assure breastfeeding. This report presents a case of an Ellis-van Creveld infant that was facing breastfeeding difficulties because of maxillary neonatal teeth. A 3 months old male infant with Ellis-van Creveld syndrome was referred to Pediatric Dentistry Department because of two upper neonatal teeth causing breastfeeding difficulties. Clinical examination revealed that teeth position was compatible to 51 and 61, and both presented uncommon ectopic soft tissue placement, conical crown and hypoplastic enamel covered by a large amount of dental biofilm. Radiography indicated they were of normal series and had 2/3 of crown completion. Due to teeth mobility that impaired breastfeeding, treatment option was exodontia. Early tooth eruption, such as in natal and neonatal teeth, by itself can't be considered a reason for exodontia. But exodontia must be considered when an early erupted tooth(s) impairs breastfeeding, especially in systemically compromised infants. In this present case report, after teeth extraction, the infant was able to breastfeed and gain weight properly.